Italy - Rechner, Amy (Minneapolis, MN : Bellwether Media, 2018)
Introduces young readers to Italy describing its landscape and climate, wildlife, people, culture, food, and more.
Includes bibliographical references (page 31) and index.
6.7
3-6
780L
Keywords: Italy -- Juvenile literature; Italy; Italy -- Social life and customs; Italy -- Social life and customs -- Juvenile literature